Changes in the stiffness of demineralized dentin following application of tooth whitening agents - Berger, Sandrine Bittencourt; Pavan, Sabrina; Pimenta Vidal, Cristina de Mattos; Santos, Paulo Henrique dos [UNESP]; Giannini, Marcelo; Bedran-Russo, Ana Karina (Informa Healthcare, 2012)
Objective. The purpose of this study was to evaluate the effect of the bleaching agents on the elastic modulus of bovine demineralized dentin matrix (EMDM). Materials and methods. Eighty-five slices were obtained from 17 bovine teeth. The slices were divided randomly into five experimental groups (n = 17): unbleached control group (CG), 4% hydrogen peroxide (HP4), 4% hydrogen peroxide + 0.05% Ca (HP4 + Ca), 7.5% hydrogen peroxide + ACP (HP7.5) and 10% carbamide peroxide (CP10). The HP4, HP4 + Ca and CP10 groups were treated with the bleaching agents for 8 h/day (14 days), while the samples of HP7.5 group were exposed to bleaching agent for 30 min twice a day (14 days). The CGwas kept in 100% humidity. After bleaching treatments, the enamel of the samples was removed and 85 dentin beams (0.5 x 1.7 x 7.0 mm) were prepared. Afterwards, the beams were immersed in 10% phosphoric acid solution (5 h) and rinsed with water (10 min). The beams were tested after 24 h, 7 and 14 days of storage in distilled water, using three-point bend method. Data were statistically analyzed using ANOVA and Fisher's test. Results. All bleaching treatments reduced the EMDM. After 14 days post-bleaching, the EMDM increased for HP4 and HP4+Ca groups. Conclusions. The use of bleaching agents promoted a decrease in EMDM, which indicates that the bleaching treatment interacts with the dentin organic matrix. The EMDM measurement for the specimens of the 7.5% hydrogen peroxide group that were immersed in water at 14 days post-bleaching did not recover the EMDM values when compared to the control group.
Keywords: elastic modulus; dentin; whitening